2012
DOI: 10.1371/journal.pone.0035382
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Cvab, an ABC Transporter Involved in the Secretion of Active Colicin V

Abstract: CvaB is the central membrane transporter of the colicin V secretion system that belongs to an ATP-binding cassette superfamily. Previous data showed that the N-terminal and C-terminal domains of CvaB are essential for the function of CvaB. N-terminal domain of CvaB possesses Ca2+-dependent cysteine proteolytic activity, and two critical residues, Cys32 and His105, have been identified. In this study, we also identify Asp121 as being the third residue of the putative catalytic triad within the active site of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…We found that both RaxB and PctB contain sequences that match the conserved C and H motifs, including the conserved Cys, His, and Asp residues (Cys28/12, His101/85, and Asp117/101 of RaxB/PctB, respectively) predicted to form the active site catalytic triad (Fig. 6A) (18,22). Additionally, they contain the conserved Gln residue (Gln22/6 of RaxB/PctB, respectively) proposed to form the oxyanion hole that stabilizes a negatively charged tetrahedral intermediate generated during amide/ester hydrolysis (Fig.…”
Section: Raxb and Pctb Carry Conserved Residues Characteristic Of Bifmentioning
confidence: 94%
See 1 more Smart Citation
“…We found that both RaxB and PctB contain sequences that match the conserved C and H motifs, including the conserved Cys, His, and Asp residues (Cys28/12, His101/85, and Asp117/101 of RaxB/PctB, respectively) predicted to form the active site catalytic triad (Fig. 6A) (18,22). Additionally, they contain the conserved Gln residue (Gln22/6 of RaxB/PctB, respectively) proposed to form the oxyanion hole that stabilizes a negatively charged tetrahedral intermediate generated during amide/ester hydrolysis (Fig.…”
Section: Raxb and Pctb Carry Conserved Residues Characteristic Of Bifmentioning
confidence: 94%
“…Additionally, they contain the conserved Gln residue (Gln22/6 of RaxB/PctB, respectively) proposed to form the oxyanion hole that stabilizes a negatively charged tetrahedral intermediate generated during amide/ester hydrolysis (Fig. 6A) (22,23). In contrast, ABC transporters that have a degenerate C39-like domain (CLD) with no proteolytic activity, such as the E. coli hemolysin transporter HlyB, do not contain the catalytically essential Cys or conserved Gln (Fig.…”
Section: Raxb and Pctb Carry Conserved Residues Characteristic Of Bifmentioning
confidence: 99%
“…The consensus sequence of cleavage of the leader peptide is L(-12)XXXE(-8)L(-7) XXXXG(-2)G(-1), where X could be any amino acids. Protein sequence analyses have shown similarity to the C39 peptidase superfamily, which has the catalytic triad Cys-His-Asp [189,190]. They are termed bifunctional ABC transporters and belong to the ABC transporter maturation secretion (AMS) superfamily, or peptidase-containing ATP-binding transporters (PCAT) [191].…”
Section: Self-immunity To Microcins Conferred By Abc Transportersmentioning
confidence: 99%
“…At the time of this review, there were no structures of either isolated class II microcin C39 peptidase domains or full transporters. Details on the function of the C39 peptidase domain come from the functional characterisation of microcin V (MccV) from E. coli [189,190] (Table 2). MccV is a class IIa microcin, and self-immunity requires a tripartite efflux system CvaA-CvaB-TolC in E. coli [192].…”
Section: Self-immunity To Microcins Conferred By Abc Transportersmentioning
confidence: 99%
“…The ABC transporters of T1SSs have recently been categorized into three groups (Kanonenberg et al ., 2013) . Group 1 transporters contain a C39 cysteine protease domain that processes NT SSs of small substrates (e.g., bacteriocins and microcins) (Havarstein et al ., 1995, Wu & Tai, 2004, Nishie et al ., 2009, Wu et al ., 2012). Group 2 transporters contain a C39-like domain, which is proteolytically inactive due to a conserved Tyr residue replacing Cys within the peptidase active site (Kotake et al ., 2008, Ishii et al ., 2010, Lecher et al ., 2012).…”
Section: Sec-independent Secretory Pathwaysmentioning
confidence: 99%